Personality and parental rearing practices as predictors of adolescent emotional and behavioral problems: Gender differences in predictive accuracy - Žukauskienė, Rita; Malinauskienė, Oksana (Psichologija, 2008)
Many models of psychological development are based on the assumption that parent’s actions are linked to, or the cause of, a child’s behavior. Information about childhood experiences, particularly parental rearing behaviour, is of importance in the clinical investigation of adjustment problems in adolescence. It has been well documented that adolescents run a heightened risk for emotional and behavioral problems when they feel rejected or overprotected by their parents and that parental rejection and overprotection has different effects for gender in developing emotional and behavioral problems. In general, the perceptions of early negative parental behavior are found to be connected to maladjustment and problem behaviors with internalizing as well as externalizing symptoms in adolescence. High perceived parental overinvolvment, rejection, and low emotional warmth correlates with low adjustment and low selfesteem, externalizing disorders, childhood depression, obsession-compulsion, and psychosomatic complaints, and parental control and absence of autonomy is connected with anxiety disorders. Adolescent delinquents perceived their parents as more rejecting, overprotecting, and less emotionally warm than normal adolescents. The perceptions of parental rejection and overprotection in the group of adolescent delinquents also correlated with attention and social problems and somatic complaints. Whether personality in combination with gender plays a role in the association between parental rejection and overprotection and emotional and behavioral problems has not yet received much attention. This study focuses on assessment of personality and parental rearing practices as predictors of adolescent emotional and behavioral problems and gender differences in predictive accuracy of emotional and behavioral problems. Data is used from longitudinal study on development of adjustment problems from childhood to adolescence. A total of 467 adolescent (251 girls and 216 boys), ages 16–17, completed questionnaires about parental rearing practices EMBU (The Egna Minnen Betraffande Uppfostran for Children, Arrindell et al., 1999). EMBU is a short 34-item questionnaire that intends to measure children and adolescents’ perception of three main aspects of parental rearing behaviour: Emotional Warmth, Rejection and Overprotection. Adolescents also completed questionnaires about their emotional and behavioral problems (YSR 11/18, Achenbach, 1991), and personality traits (NEO-FFI, Costa and McCrae, 1992). Girls scored higher on emotional problems (but not on behavioral problems) than boys. Parental behavior was more strongly associated with girls’ emotional and behavioral problems, in comparison to boys. Regression analysis revealed that parental rearing behavior is less significant predictors of emotional and behavioral problems in adolescence, than personality traits. Furthermore, parental rearing behavior and personality traits (namely, neuroticizm) were stronger predictors of emotional and behavioral problems for girls in comparison to boys. Overall, parental rearing practices and personality traits of adolescents are better predictors for emotional and behavioral problems of girls in comparison to boys.